1/3 (6x - 9) = -33

9 answers

To solve the equation:

1/3(6x - 9) = -33

First, distribute 1/3 to (6x - 9):

2x - 3 = -33

Next, add 3 to both sides of the equation to isolate the variable term:

2x = -30

To remove the coefficient of 2, divide both sides of the equation by 2:

x = -30/2

Simplifying the expression:

x = -15

Therefore, the solution to the equation is x = -15.
-3/5 (15x - 30) = 198
To solve the equation:

-3/5(15x - 30) = 198

First, distribute -3/5 to (15x - 30):

-9x + 18 = 198

Next, subtract 18 from both sides of the equation to isolate the variable term:

-9x = 180

To remove the coefficient of -9, divide both sides of the equation by -9:

x = 180/(-9)

Simplifying the expression:

x = -20

Therefore, the solution to the equation is x = -20.
3(4x - 12) = 84
To solve the equation:

3(4x - 12) = 84

First, distribute 3 to (4x - 12):

12x - 36 = 84

Next, add 36 to both sides of the equation to isolate the variable term:

12x = 120

To remove the coefficient of 12, divide both sides of the equation by 12:

x = 120/12

Simplifying the expression:

x = 10

Therefore, the solution to the equation is x = 10.
20 (2x - 8) = 440
To solve the equation:

20(2x - 8) = 440

First, distribute 20 to (2x - 8):

40x - 160 = 440

Next, add 160 to both sides of the equation to isolate the variable term:

40x = 600

To remove the coefficient of 40, divide both sides of the equation by 40:

x = 600/40

Simplifying the expression:

x = 15

Therefore, the solution to the equation is x = 15.
0.72=0.4 (x + 1.4)
To solve the equation:

0.72 = 0.4(x + 1.4)

First, distribute 0.4 to (x + 1.4):

0.72 = 0.4x + 0.56

Next, subtract 0.56 from both sides of the equation to isolate the variable term:

0.72 - 0.56 = 0.4x

0.16 = 0.4x

To remove the coefficient of 0.4, divide both sides of the equation by 0.4:

0.16/0.4 = x

0.4 = x

Therefore, the solution to the equation is x = 0.4.